Rural Households’ Demand Status for Mitigation of Prosopis juliflora (Sw.) DC Invasion and Its Determinant Factors in Ethiopia: Empirical Evidence from Afar National Regional State - Kindineh Sisay; Ketema Bekele; Jema Haji; Urs Schaffner (The Scientific World Journal)
Ethiopia is among the world’s poorest nations, and its economy is growing extremely slowly; thus, the government’s budget to manage environmental amenities is not always sufficient. Thus, for the provision of environmental management services such as the eradication of Prosopis juliflora, the participation of local households and other stakeholders is crucial. This study is therefore initiated with the objective of assessing rural households’ demands for mitigating Prosopis juliflora invasion in the Afar Region of Ethiopia. A multistage sampling technique was employed to obtain the 313 sample rural households that were used in the analysis, and those sample households were selected randomly and independently from the Amibara and Awash Fentale districts of Afar National Regional State, Ethiopia. In doing this, a seemingly unrelated bivariate probit model was used to determine factors affecting rural households’ demands for mitigating Prosopis juliflora invasion. Consequently, as per the inferential statistical results, there was a significant mean/percentage difference between willing and nonwilling households for the hypothesized variables, except for some variables such as farm experience; years lived in the area, distance from the market, and dependency ratio. Furthermore, the seemingly unrelated bivariate probit model result indicates that sex, family size, tenure security, livestock holding, frequency of extension contact, and years lived in the area were important factors influencing the willingness to participate in Prosopis juliflora management practices positively, whereas age, off-farm/nonincome, and bid value affected willingness to pay negatively and significantly. Hence, to improve the participation level of households, policymakers should target these variables.